Iron phosphate positive electrode material, preparation method and application thereof
Patent Information
- Application Number
- CN202611316505.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-28
- Publication Date
- 2026-10-16
AI Technical Summary
本发明以橄榄石结构磷酸铁锂作为结构模板,通过氧化剂溶液进行化学氧化脱锂,使磷酸铁锂中的锂离子脱出并形成磷酸铁,同时基本保留原有的橄榄石型磷酸盐骨架,减少了由传统磷酸铁前驱体重新构筑橄榄石结构所需的固相重构过程。XRD测试结果表明,所得产物具有与Heterosite相FePO4相吻合的特征峰,且相对于原始磷酸铁锂,其121晶面和131晶面间距减小,说明化学脱锂后晶体骨架得到有效继承。
Smart Images

Figure CN122916084A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery technology, and in particular to an iron phosphate cathode material, its preparation method, and its application. Background Technology
[0002] Lithium iron phosphate (LiFePO4) with an olivine structure possesses high safety, good cycle stability, and long lifespan, and is widely used in power batteries and energy storage batteries. During charging, lithium iron phosphate releases lithium ions to form an iron phosphate (FePO4) phase, and the two phases share an interconnected phosphate framework structure. Besides being a commonly used precursor for lithium iron phosphate preparation, the crystal structure, particle morphology, and ion transport channels of iron phosphate itself also affect its electrochemical reaction kinetics when used as an electrode active material. Therefore, obtaining structurally stable, highly reactive iron phosphate materials that can be directly used as battery cathodes is of great significance for improving the electrochemical performance of phosphorus-based cathode materials.
[0003] Existing battery-grade iron phosphate is typically prepared using iron salts and phosphorus sources as raw materials through steps such as precipitation, aging, filtration, washing, drying, and calcination. For example, invention patent CN 110510593 A discloses a method for preparing an iron phosphate precursor and lithium iron phosphate. This method obtains an iron phosphate dihydrate precursor by adjusting the pH and temperature of the reaction system, and then obtains anhydrous iron phosphate through calcination. This iron phosphate is then used as a precursor to prepare lithium iron phosphate. The main focus is on controlling the particle morphology and tap density of the iron phosphate precursor. The preparation process includes precipitation reaction, aging, and high-temperature calcination. The resulting iron phosphate is primarily used as a raw material for subsequent synthesis of lithium iron phosphate, and is not designed for the direct application of iron phosphate as a positive electrode active material.
[0004] In addition, existing technologies have attempted to obtain iron phosphate from lithium iron phosphate through delithiation. Patent CN 116281933 A discloses a fluorinated iron phosphate material, its preparation method, and its application. This method involves first placing a lithium iron phosphate electrode in an aqueous electrolyte, then electrochemically delithicing it under an applied voltage to obtain iron phosphate material, followed by plasma-enhanced chemical vapor deposition (PECVD) for fluorination. While this method can utilize the delithiation reaction of lithium iron phosphate to obtain iron phosphate, it requires pre-preparation of the electrode, configuration of an electrochemical delithiation device with voltage control, and subsequent fluorination treatment. The process and equipment requirements are relatively high, making it unsuitable for the direct and convenient mass production of iron phosphate powder.
[0005] Regarding the resource utilization of waste lithium iron phosphate, invention patent CN 113880064 A discloses a method for treating high-impurity lithium iron phosphate waste powder with low phosphoric acid consumption. After removing binders and aluminum impurities, it uses phosphoric acid and hydrogen peroxide in an acidic system with a pH of 2-3 for oxidative leaching, allowing lithium to selectively enter the solution and obtaining iron phosphate leaching residue. Subsequently, it is necessary to replenish iron source and oxidant, purify with excess phosphoric acid, and calcine at high temperature to obtain battery-grade iron phosphate. Its main purpose is to recover lithium, iron, and phosphorus and remove impurities from waste lithium iron phosphate. The process relies on acid leaching, impurity removal, purification, and calcination steps, which still differs from the technical requirements for directly preparing high-activity iron phosphate cathode materials from olivine-structured lithium iron phosphate.
[0006] Therefore, it is still necessary to provide a method for preparing iron phosphate cathode materials with a relatively simple process, mild reaction conditions, and easy scale-up, so that olivine-structured lithium iron phosphate can be delithiated chemically without the need for pre-fabricated electrode sheets, external electric fields, or high-temperature crystal reconstruction, and the original olivine framework structure can be basically maintained after delithiation, thereby obtaining iron phosphate materials that can be directly used as positive electrode active materials for lithium-ion batteries and have high specific capacity and rate performance. Summary of the Invention
[0007] In view of this, the present invention provides an iron phosphate cathode material, its preparation method, and its application. The present invention obtains an iron phosphate cathode material by contacting olivine-structured lithium iron phosphate with an oxidant solution and performing chemical oxidation delithiation, while essentially maintaining the original olivine framework structure. This achieves a simple conversion from lithium iron phosphate to an iron phosphate cathode material with high reactivity and good rate performance, and has promising application prospects in the preparation of high-performance lithium-ion battery cathode materials and the industrialization of phosphorus-based cathode materials.
[0008] The first aspect of this invention provides a method for preparing an iron phosphate cathode material, comprising the following steps: Lithium iron phosphate with olivine structure was added to an oxidant solution and stirred at 0-95°C. After the reaction was completed, the mixture was washed, filtered and dried to obtain the iron phosphate cathode material.
[0009] Preferably, the oxidant solution is prepared by weighing the oxidant at room temperature, dissolving it, and then transferring it to a volumetric flask and making up to volume; the concentration of the oxidant solution is 0.1~50 g / L; the oxidant includes at least one of inorganic and organic oxidants, wherein the inorganic oxidant includes ammonium persulfate, sodium persulfate, potassium persulfate, hydrogen peroxide, ferric chloride, and potassium permanganate, and the organic oxidant includes peracetic acid, tert-butyl hydroperoxide, and benzoyl peroxide.
[0010] Preferably, the olivine-structured lithium iron phosphate is a carbon-coated olivine-structured lithium iron phosphate.
[0011] Preferably, the solid-liquid ratio of the olivine-structured lithium iron phosphate to the oxidant solution is 1 g: 10~200 mL.
[0012] Preferably, the stirring speed is 100~1000 rpm and the stirring reaction time is 0.5~24 h.
[0013] Preferably, the washing process involves alternating between deionized water and anhydrous ethanol until the pH of the washing solution is neutral.
[0014] Preferably, the drying is performed using at least one of forced-air drying and vacuum drying, with a drying time of 1 to 24 hours and a drying temperature of 50 to 130°C.
[0015] A second aspect of the present invention provides an iron phosphate cathode material prepared by the above method, wherein the cathode material is obtained by chemical oxidation delithiation of olivine-structured lithium iron phosphate, and basically maintains the olivine crystal structure of the original lithium iron phosphate; relative to the original lithium iron phosphate, the spacing between the 121 and 131 crystal planes of the iron phosphate cathode material is reduced.
[0016] Preferably, the iron phosphate cathode material has a capacity of not less than 170 mAh / g at a 0.1 C rate and a capacity of not less than 160 mAh / g at a 1 C rate.
[0017] A third aspect of the present invention provides the application of the aforementioned iron phosphate cathode material in lithium-ion batteries.
[0018] Compared with the prior art, the beneficial technical effects of the present invention are as follows: This invention uses olivine-structured lithium iron phosphate as a structural template and performs chemical oxidation delithiation using an oxidant solution. This process removes lithium ions from the lithium iron phosphate and forms iron phosphate, while largely preserving the original olivine-type phosphate framework. This reduces the solid-state reconstruction process required to rebuild the olivine structure from traditional iron phosphate precursors. XRD results show that the obtained product has characteristic peaks consistent with the heterosite phase FePO4, and the interplanar spacing between its 121 and 131 crystal planes is reduced compared to the original lithium iron phosphate, indicating that the crystal framework is effectively inherited after chemical delithiation.
[0019] Because the obtained iron phosphate cathode material inherits the olivine structure and corresponding lithium-ion migration channels of lithium iron phosphate, it can directly participate in the insertion and extraction of lithium ions as a cathode active material, which is beneficial to improving the material's reactivity and rate performance. In the example tests, the specific capacity of the material obtained by this invention reached 173 mAh / g and 160 mAh / g at 0.1 C and 1 C rates, respectively; the overall test results also show that the discharge specific capacity of the material obtained by this invention at 0.1 C rate is 5%~10% higher than that of the comparative example, demonstrating better electrochemical performance.
[0020] This invention uses solution chemical oxidation to complete lithium removal. The reaction temperature can be adjusted within the range of 0~95℃. After the reaction is completed, the target material can be obtained by washing, filtering and drying. There is no need to pre-make lithium iron phosphate into electrode sheets and apply an external voltage, nor is there a need for high-voltage reaction or special protective atmosphere. This reduces the need for electrochemical lithium removal equipment and traditional high-temperature crystal reconstruction steps. The process is shorter, the reaction conditions are mild and easy to control.
[0021] This invention can use a variety of inorganic or organic oxidants such as persulfate, peroxide, ferric chloride, and potassium permanganate. The delithiation process can be adjusted by parameters such as oxidant concentration, solid-liquid ratio, stirring speed, and reaction time. The process is highly adaptable and can be easily optimized according to the state of raw materials and production scale. It has the potential for further industrial scale-up and application. Attached Figure Description
[0022] The present invention will be further described below with reference to the accompanying drawings.
[0023] Figure 1 This is a comparison of the Fourier transform infrared (FT-IR) spectra of the iron phosphate cathode material obtained in Example 1 of the present invention and commercial iron phosphate. Figure 2 The images shown are scanning electron microscope (SEM) images of commercial lithium iron phosphate and iron phosphate cathode material in Example 1 of this invention, where the left image is commercial lithium iron phosphate and the right image is iron phosphate cathode material. Figure 3 The image shows the X-ray diffraction (XRD) pattern of the iron phosphate cathode material obtained in Example 1 of this invention and its comparison with the standard diffraction card PDF#37-0478. Figure 4 This is a comparison of the charge-discharge curves of the iron phosphate cathode material obtained in Example 1 of the present invention and the commercial lithium iron phosphate in Comparative Example 1 at a rate of 0.1 C. Figure 5 This is a comparison chart of the rate performance of the iron phosphate cathode material obtained in Example 1 of the present invention and the commercial lithium iron phosphate in Comparative Example 1. Detailed Implementation
[0024] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0025] Unless otherwise specified, all experiments were repeated three times, and the results are expressed as averages.
[0026] Example 1 S1. Weigh 2.5 g of ammonium persulfate at room temperature, dissolve it in deionized water, transfer it to a 250 mL volumetric flask and make up to volume to obtain an oxidizing agent solution with a concentration of 10 g / L. S2. Weigh 2 g of lithium iron phosphate powder and add it to 200 mL of ammonium persulfate solution at a solid-liquid ratio of 1 g: 100 mL. S3. Stir the reaction at 400 rpm for 6 h at room temperature; S4. After the reaction is complete, wash the product with deionized water and anhydrous ethanol alternately until the pH of the washing solution is neutral. S5. Place the filtered product in a forced-air drying oven and dry it at 80°C for 8 h to obtain a highly active iron phosphate cathode material (OFP) with an olivine structure.
[0027] S6. Using the obtained olivine-structured high-activity iron phosphate cathode material as the cathode active material, a homogenization process was carried out for 10 h at a ratio of active material: conductive carbon black: PVDF = 8:1:1. The resulting slurry was coated and cut into sheets. Batteries were assembled using high-activity iron phosphate as the cathode material, lithium foil as the anode material, and lithium hexafluorophosphate as the electrolyte, with copper foil and aluminum foil as the anode and cathode current collectors, respectively. Electrochemical performance tests were conducted at room temperature. The test results are shown below. Figure 4 and Figure 5 .
[0028] At stepwise rate increases of 0.1 C, 0.2 C, 0.5 C, 1 C, 2 C, 5 C, 10 C, and 0.1 C, the battery capacities composed of the described lithium iron phosphate cathode material were 173 mAh / g, 170 mAh / g, 165 mAh / g, 160 mAh / g, 155 mAh / g, 130 mAh / g, 90 mAh / g, and 173 mAh / g, respectively. Compared with batteries composed of commercial lithium iron phosphate (CLFP) battery materials, the capacity increased by 5%, 7%, 9%, 12%, 11%, 20%, 10%, and 5% at the corresponding rate increases, demonstrating excellent electrochemical performance.
[0029] Example 2 The difference from Example 1 is that ammonium persulfate was replaced with sodium persulfate. 2.5 g of sodium persulfate was weighed at room temperature, dissolved in deionized water, and transferred to a 250 mL volumetric flask and diluted to volume to obtain an oxidant solution with a concentration of 10 g / L. 2 g of lithium iron phosphate powder was weighed and added to 200 mL of the sodium persulfate solution at a solid-liquid ratio of 1 g:100 mL. The reaction was stirred at 450 rpm for 6.5 h at room temperature. The product was washed alternately with deionized water and anhydrous ethanol until neutral, filtered, and then dried in a forced-air drying oven at 80°C for 8 h to obtain the target product.
[0030] The electrochemical testing method was the same as in Example 1. At 0.1 C, 0.2 C, 0.5 C, 1 C, 2 C, 5 C, 10 C, and 0.1 C, the capacities were 171 mAh / g, 168 mAh / g, 163 mAh / g, 159 mAh / g, 153 mAh / g, 127 mAh / g, 89 mAh / g, and 172 mAh / g, respectively. Compared to lithium iron phosphate battery materials, the capacities increased by 4%, 6%, 8%, 10%, 9%, 17%, 9%, and 4%, respectively, demonstrating excellent electrochemical performance.
[0031] Example 3 The difference from Example 1 is that the oxidant was replaced with potassium persulfate. 2.5 g of potassium persulfate was weighed at room temperature, dissolved in deionized water, and transferred to a 250 mL volumetric flask and diluted to volume to obtain an oxidant solution with a concentration of 10 g / L. 2 g of lithium iron phosphate powder was weighed and added to 220 mL of the potassium persulfate solution at a solid-liquid ratio of 1 g:110 mL. The reaction was stirred at 400 rpm for 7 h at room temperature. The product was washed with deionized water until neutral and dried under forced-air drying at 80°C for 7 h to obtain the target product.
[0032] The electrochemical testing method was the same as in Example 1. At 0.1 C, 0.2 C, 0.5 C, 1 C, 2 C, 5 C, 10 C, and 0.1 C, the capacities were 174 mAh / g, 171 mAh / g, 165 mAh / g, 163 mAh / g, 154 mAh / g, 132 mAh / g, 94 mAh / g, and 174 mAh / g, respectively. Compared to lithium iron phosphate battery materials, the capacities were increased by 6%, 8%, 10%, 13%, 12%, 21%, 11%, and 6%, respectively, demonstrating excellent electrochemical performance.
[0033] Example 4 The difference from Example 1 is as follows: a 30% hydrogen peroxide solution was measured at room temperature and diluted to prepare an oxidant solution with a concentration of 10 g / L (calculated as H2O2); 2 g of lithium iron phosphate powder was weighed and added to the oxidant solution at a solid-liquid ratio of 1 g: 110 mL; the mixture was stirred at 600 rpm for 8 h at room temperature. Subsequent steps were the same as in Example 1 to obtain the target product.
[0034] The electrochemical testing method was the same as in Example 1. At 0.1 C, 0.2 C, 0.5 C, 1 C, 2 C, 5 C, 10 C, and 0.1 C, the capacities were 174 mAh / g, 170 mAh / g, 165 mAh / g, 161 mAh / g, 157 mAh / g, 130 mAh / g, 90 mAh / g, and 173 mAh / g, respectively. Compared to lithium iron phosphate battery materials, the capacities were increased by 6%, 7%, 9%, 13%, 12%, 20%, 10%, and 6%, respectively, demonstrating excellent electrochemical performance.
[0035] Example 5 The difference from Example 1 is as follows: 7.5 g of ferric chloride was weighed at room temperature, dissolved in deionized water, and transferred to a 250 mL volumetric flask and diluted to volume to obtain an oxidant solution with a concentration of 30 g / L; 2 g of lithium iron phosphate powder was weighed and added to 200 mL of ferric chloride solution at a solid-liquid ratio of 1 g:100 mL; the mixture was stirred at 600 rpm for 6 h at room temperature. Subsequent steps were the same as in Example 1 to obtain the target product.
[0036] The electrochemical testing method was the same as in Example 1. At 0.1 C, 0.2 C, 0.5 C, 1 C, 2 C, 5 C, 10 C, and 0.1 C, the capacities were 172 mAh / g, 169 mAh / g, 164 mAh / g, 159 mAh / g, 154 mAh / g, 129 mAh / g, 88 mAh / g, and 172 mAh / g, respectively. Compared to lithium iron phosphate battery materials, the capacities were increased by 5%, 6%, 8%, 11%, 11%, 19%, 10%, and 5%, respectively, demonstrating excellent electrochemical performance.
[0037] Example 6 The difference from Example 1 is as follows: 12.5 g of peracetic acid was weighed at room temperature, dissolved in deionized water, and transferred to a 250 mL volumetric flask and diluted to volume to obtain an oxidant solution with a concentration of 50 g / L; 2 g of lithium iron phosphate powder was weighed and added to 200 mL of the peracetic acid solution at a solid-liquid ratio of 1 g:100 mL; the mixture was stirred at 600 rpm for 4 h at room temperature. Subsequent steps were the same as in Example 1 to obtain the target product.
[0038] The electrochemical testing method was the same as in Example 1. At 0.1 C, 0.2 C, 0.5 C, 1 C, 2 C, 5 C, 10 C, and 0.1 C, the capacities were 170 mAh / g, 169 mAh / g, 163 mAh / g, 156 mAh / g, 150 mAh / g, 127 mAh / g, 85 mAh / g, and 170 mAh / g, respectively. Compared to lithium iron phosphate battery materials, the capacities were increased by 4%, 5%, 8%, 10%, 10%, 15%, 9%, and 4%, respectively, demonstrating excellent electrochemical performance.
[0039] Example 7 The difference from Example 1 is as follows: 6.25 g of benzoyl peroxide was weighed at room temperature, dissolved in deionized water, and transferred to a 250 mL volumetric flask and diluted to volume to obtain an oxidant solution with a concentration of 25 g / L; 2 g of lithium iron phosphate material was weighed and added to 360 mL of benzoyl peroxide solution at a solid-liquid ratio of 1 g:180 mL; the mixture was stirred at 400 rpm for 10 h at room temperature. Subsequent steps were the same as in Example 1 to obtain the target product.
[0040] The electrochemical testing method was the same as in Example 1. At 0.1 C, 0.2 C, 0.5 C, 1 C, 2 C, 5 C, 10 C, and 0.1 C, the capacities were 173 mAh / g, 170 mAh / g, 165 mAh / g, 162 mAh / g, 157 mAh / g, 130 mAh / g, 90 mAh / g, and 173 mAh / g, respectively. Compared to lithium iron phosphate battery materials, the capacities were increased by 5%, 7%, 9%, 13%, 12%, 20%, 10%, and 5%, respectively, demonstrating excellent electrochemical performance.
[0041] Structural characterization and application testing: X-ray diffraction (XRD) tests were performed on the materials described in Examples 1-7 and Comparative Example 1. The results showed that Comparative Example 1 has a typical lithium iron phosphate structure, and the products of Examples 1-7 exhibited characteristic peaks in the 20-30 ° diffraction range that are consistent with the Heterosite phase FePO4, confirming that they maintain the olivine crystal structure.
[0042] Electrochemical tests show that the iron phosphate cathode materials used in Examples 1-7 have a discharge specific capacity that is more than 4% higher than that of Comparative Example 1 at a 0.1 C rate, and a 1 C capacity that is more than 10% higher. This indicates that the iron phosphate cathode materials have high reactivity.
[0043] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.
Claims
1. A method for preparing an iron phosphate cathode material, characterized in that, Includes the following steps: Lithium iron phosphate with olivine structure was added to an oxidant solution and stirred at 0-95°C. After the reaction was completed, the mixture was washed, filtered and dried to obtain the iron phosphate cathode material.
2. The preparation method according to claim 1, characterized in that, The concentration of the oxidant solution is 0.1~50 g / L; the oxidant includes at least one of inorganic oxidants and organic oxidants; the inorganic oxidant includes at least one of ammonium persulfate, sodium persulfate, potassium persulfate, hydrogen peroxide, ferric chloride and potassium permanganate; the organic oxidant includes at least one of peracetic acid, tert-butyl hydroperoxide and benzoyl peroxide.
3. The preparation method according to claim 1, characterized in that, The olivine-structured lithium iron phosphate is a carbon-coated olivine-structured lithium iron phosphate.
4. The preparation method according to claim 1, characterized in that, The solid-liquid ratio of the olivine-structured lithium iron phosphate to the oxidant solution is 1 g: 20~200 mL.
5. The preparation method according to claim 1, characterized in that, The stirring speed of the stirring reaction is 100~1000 rpm, and the stirring reaction time is 0.5~24 h.
6. The preparation method according to claim 1, characterized in that, The washing process involves alternating between deionized water and anhydrous ethanol until the pH of the washing solution is neutral.
7. The preparation method according to claim 1, characterized in that, The drying process employs at least one of forced-air drying and vacuum drying, with a drying temperature of 50~130℃ and a drying time of 1~24 h.
8. The iron phosphate cathode material prepared by the method according to any one of claims 1 to 7, characterized in that, The iron phosphate cathode material is obtained by chemical oxidation and delithiation of olivine-structured lithium iron phosphate, and basically retains the original olivine crystal structure of lithium iron phosphate; compared with the original lithium iron phosphate, the spacing between the 121 and 131 crystal planes of the iron phosphate cathode material is reduced.
9. The iron phosphate cathode material according to claim 8, characterized in that, The iron phosphate cathode material has a capacity of not less than 170 mAh / g at 0.1 C rate and not less than 160 mAh / g at 1 C rate.
10. The application of the iron phosphate cathode material according to claim 8 in lithium-ion batteries.
Citation Information
Patent Citations
Method for preparing ferric phosphate precursor and lithium iron phosphate
CN110510593A
Method for treating high-impurity lithium iron phosphate waste powder by using low-consumption phosphoric acid
CN113880064A
Ferric fluorophosphate material as well as preparation method and application thereof
CN116281933A